Utilising Java technology with CORBA for medical informatics / Ahmad Shukri M Noor … [et al.] - M Noor, Ahmad Shukri; Mohd Saman, Md Yazid; Deris, Mustafa M.; Manap, Sarif A (2006)
We are conducing research and developing a distributed multimedia database system for medical informatics to be used by the mobile physician. The ability the java based web application to distribute information to geographically distant users on a wide variety of computers. Makes it an obvious candidate for a technological solution for distributed medical informatics systems. This paper describes how to use Java tools and extensions, like the Java Media Framework (JMF), Java Swing, Java Foundation Class (JFC) and JDBC. This Java technology is utilized with Common Object Request Broker Architecture (CORBA) in order to develop a medical informatics systems model in distributed environments. This model is utilized java as client application and server application java also can be used as client applet in web browsers. Furthermore we integrate java with CORBA as middleware that sit in middle-tier and IBM DB2 relational database at the server side.